On quasi h-pure submodules of QTAG-modules - Mohd. Z. Khan; A. Zubair (International Journal of Mathematics and Mathematical Sciences)
Different concepts and decomposition theorems have been done for QTAG-modules by number of authors. We introduce quasi h-pure submodules for QTAG-modules and we obtain several characterizations for quasi h-pure submodules and as a consequence we deduce a result done by Fuchs 1973.